6x-99=-5x

Simple and best practice solution for 6x-99=-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-99=-5x equation:


Simplifying
6x + -99 = -5x

Reorder the terms:
-99 + 6x = -5x

Solving
-99 + 6x = -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-99 + 6x + 5x = -5x + 5x

Combine like terms: 6x + 5x = 11x
-99 + 11x = -5x + 5x

Combine like terms: -5x + 5x = 0
-99 + 11x = 0

Add '99' to each side of the equation.
-99 + 99 + 11x = 0 + 99

Combine like terms: -99 + 99 = 0
0 + 11x = 0 + 99
11x = 0 + 99

Combine like terms: 0 + 99 = 99
11x = 99

Divide each side by '11'.
x = 9

Simplifying
x = 9

See similar equations:

| 4(x-1)+3(x+1)= | | 217.25=3 | | 4x-(2x+5)=3x-10 | | 6m-6=6m+18 | | 2x+3x+3=-12 | | 21p-62=38+p | | 8x+12-2x-5=3 | | y=kx+f | | 2(2+5x)=9(x-1) | | 81c^2+18c+1= | | 9[5-7(x-1)]+6[(5x+7)-8]=11x-336 | | (1-5j)+(-2-6j)=-1-11j | | 6x+x^2=84 | | 9c^2-8c-1= | | 4-x=4x+19 | | -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= | | 15z+30=15y+30 | | 6(W+3)=-2(5W-5)+2W | | 3(9+1)-5=(2y-2) | | k-7=10k-16 | | x^3-4x^2+x-9=0 | | 3i+10=14i-12 | | n^2-81= |

Equations solver categories